Pengaruh Budaya Organisasi, Kepuasan Kerja, dan Gaya Kepemimpinan Terhadap Komitmen Organisasi PT BCA Tbk. KCU Bekasi - Shilastio; Asrul; Andi Muhammad Sadli (Mulia Pratama, 2023)
The writing of this thesis is the result of a survey at PT BCA, Tbk. KCU Bekasi by discussing how far the influence of organizational culture, job satisfaction and leadership style on organizational commitment. PT BCA. Tbk, KCU Bekasi has 122 workers with various cultural, educational and age backgrounds. With a relatively large number of employees, of course there are various kinds of conflicts which eventually make workers leave the company or in other words have low organizational commitment. Based on the above, the problem to be discussed in writing this thesis is entitled “The Influence of Organizational Culture, Job Satisfaction and Leadership Style on PT BCA's Organizational Commitment. Tbk, Bekasi Branch Office." With the formulation of the problem above, it is obtained a linear regression value of Y = 0.480 + 1.006 X1 + 0.155 X2 - 0.128 X3, a correlation coefficient of Ry123 of 0.855 and a coefficient of determination of 0.716. These results indicate that the magnitude of the increase in organizational commitment of PT BCA, Tbk. KCU Bekasi (Y) caused by organizational culture (X1), job satisfaction (X2) and leadership style (X3) is 71.6%, while 28.4 is influenced by other factors. This means that the relationship between X1, X2, X3 and Y is very strong and positive. These results also show that the majority of employees agree that organizational culture greatly influences their organizational commitment at PT BCA, Tbk. KCU Bekasi.